ANALISIS RUSAKNYA SEAT RING VALVE TERHADAP CARGO OIL PUMP DI MT. TRANSKO ANTASENA - Surya; Bayu Yudho Baskoro; Achmad Ali Mashartanto; Elfira Wirza; Kurniawan Abadi (STKIP Subang, 2026)
This study aims to analyze the causes of seat ring valve damage and its impact on the performance of the cargo oil pump aboard MT. Transko Antasena, as well as the efforts to overcome the issue. The research was motivated by a discharge delay during unloading of RON 90 cargo at Pare-Pare Port caused by leakage in the seat ring valve of tank 4P/S. A qualitative descriptive method was used, with data collected through observation, interviews, and documentation during the Sea Project period. Data were analyzed using the Fishbone diagram approach. The results show that the damage was caused by improper valve operation, component wear and corrosion, inconsistent SOP implementation, material limitations, environmental factors, and inadequate maintenance. The impacts include backflow, unstable pump pressure, decreased pump efficiency, discharge delays, and potential safety risks. Proposed solutions include improving crew competence, strengthening supervision, conducting routine maintenance, selecting appropriate materials, controlling environmental conditions, and optimizing the Planned Maintenance System (PMS). These efforts are expected to improve discharge efficiency and prevent similar incidents.